North American Free Trade Agreement : Canadian statement on implementation (Queen's Printer for Canada OttawaCA, 1992)
Sets out the Government of Canada's general approach to trade policy in the 1990s, the role of the NAFTA in that context, and the Government's interpretation of the rights and obligations contained within the Agreement and reflected in the NAFTA Implementation Act of 1993, and the specific goals and measures the Government will pursue.
Extract Canada Gazette, Part I January 1, 1994